Analisis Bahasa Figuratif Kiasan dalam Album Nonfiksi Karya Juicy Luicy - Niswati, Khairun; Azhari, Teuku; Harliyana, Iba (FKIP Universitas Palangka Raya, 2026)
This study aims to describe the types of figurative language and reveal the meanings contained in the song lyrics of the Nonfiksi album by Juicy Luicy. This research employed a qualitative approach with a descriptive-analytical method. The research data consisted of excerpts of song lyrics containing figurative language found in the Nonfiksi album. Data collection techniques were carried out through reading and note-taking techniques, while data analysis used the Miles and Huberman model, which includes data collection, data reduction, data presentation, and conclusion drawing. The results of the study found 68 instances of figurative language, consisting of 2 similes, 21 metaphors, 3 allegories, 6 personifications, 3 epithets, 3 synecdoches, 2 hypallages, 5 ironies, 3 cynicisms, 1 sarcasm, 10 satires, and 9 innuendos. The meanings contained in the figurative language describe feelings of love, loss, disappointment, regret, and emotional conflicts in interpersonal relationships.